Pengaruh Minat Anak Dalam Menonton Acara Televisi Terhadap Perilaku Sosial Anak Kelompok B Di TK PGRI Doplang - Ayu Murni SA, Dyah; , Drs. Haryono Yuwono, M.Pd (2016)
This research aims to know the significant influence between the child's interest in watching television shows against the social behavior of the child Group B in kindergarten Doplang PGRI. The methods used in this research is the study of comparisons with experimental design Treatments By Subjects or simply pattern Design of T-S. The subject of this research is the son of Group B TK PGRI Doplang year 2015/2016 lessons totalling 34. Engineering data collection using the child's social behavior observation. Technique of data analysis used comparative analysis of t-test-test to tell the difference of the average values of the test results. results showed the calculation of the value of social behavior before being given the film's television program to watch Upin and Ipin-Adit & Sopo Jarwo (pre test) and after watching the television program was given the film Upin and Ipin-Adit & Sopo Jarwo (post test) generated Asymp. Sig (2-tailed) = 0.000 with the significance level (α) = thitung and 5% 18.180. Based on this data can be inferred Asymp. Sig (2-tailed) < 0.05 and 18.180 thitung > ttabel 2.042. Based on the results of the study it can be concluded that: the child's interest in watching television shows shown to improve children's social behavior Group B KINDERGARTEN lesson Doplang year 2015/2016. The more often children watching television shows film of Upin and Ipin-Adit & Sopo Jarwo, increasing also the social behavior of the child.